A scarce case: Co-occurrence of neurofibromatosis type 1 and Klinefelter syndrome - Haniyeh Rahbar Kafshboran; Neşe Akcan; Doğa Ceren Polat; Mahmut Çerkez Ergören (Global Medical Genetics)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder with a heterogeneous group of symptoms, including characteristic cafe-au-lait macules, axillary or inguinal freckling, Lisch nodules, as well as skeletal deformation, scoliosis, mental retardation, and tumors of the nervous system. Klinefelter syndrome (KS) is a gonadal dysgenesis, with symptoms in males, including an extra X chromosome, leading to tall stature, hypogonadism, and infertility. Although the co-occurrence of NF1 and KS is a rare finding, this report describes this unique entity detected in an eight-year-old boy with numerous hyperpigmentation spots, a multitude of skin and subcutaneous nodules, seizures, arterial stenosis, and mild gynecomastia. Whole-exome sequencing (WES) was conducted along with copy number analysis for the proband and his parents. Multiplex Ligation-dependent Probe Amplification (MLPA) is used to validate the copy number variations detected by next-generation sequencing (NGS). The results showed a pathogenic heterozygous mutation (c.246_247del, p.Gln83Valfs*23) in a human neurofibromin 1 gene (NF1), detected in the proband and his father, whilst the genetic analysis performed by the karyotype revealed a copy gain of the X chromosome (47, XXY) leading to KS. This rare occurrence of NF1 with co-occurrence of KS may raise some concerns and difficulties in the clinical management of this case, particularly Testosterone hormone replacement therapy and the potential risks of malignancies. Therefore, clinicians may ask for KS genetic tests in male patients with NF1 who have symptoms of gynaecomasia or infertility, and closely monitor for potential malignancies and other complications. Compellingly, this case emphasizes the importance of advanced genetic analysis in providing genetic tools for diagnosing and managing individuals with rare and complex syndromes with overlapping clinical features. Early detection and comprehensive clinical interventions are the key cornerstones to improving patient outcomes.